Elevation of Microglial Basic Fibroblast Growth Factor Contributes to Development of Neuropathic Pain after Spinal Nerve Ligation in Rats. Issue 3 (February 2016) - Fujimaki, Hisako; Inoue, Gen; Uchida, Kentaro; Miyagi, Masayuki; Saito, Wataru; Sato, Asako; Takaso, Masashi
Abstract : Study Design: Reverse transcriptase-polymerase chain reaction (RT-PCR) and immunohistological analysis of spinal cord and pain behavior analysis in a rat neuropathic pain model were conducted to examine the function of microglial basic fibroblast growth factor (bFGF) in the development of neuropathic pain. Objective: To investigate the role of bFGF in spinal microglia during the development of allodynia following spinal nerve ligation in rats. Summary of Background Data: Evidence suggests that the production of bFGF by spinal cord glial cells is increased in response to peripheral nerve injury. Although an association between bFGF and astrocytes has been widely reported, the relationship between bFGF and microglia, particularly with respect to the development of neuropathic pain, remains poorly understood. Methods: Spinal nerve ligation rats were used. After surgery, bFGF expression in the spinal cord was investigated using RT-PCR and immunohistochemistry. Neutralizing antibodies to bFGF were injected intrathecally into rats after spinal nerve ligaton. Spinal cords were used for RT-PCR analysis and pain behavior was analyzed using the von Frey test. Results: bFGF mRNA expression was significantly increased in the spinal cord 6 hours after spinal nerve ligation compared with untreated rats. Immunohistochemical analysis revealed that bFGF co-localized with ionized calcium-binding adaptor molecule 1, a microglial marker, and myeloperoxidase. Neutralizing antibodies to bFGF attenuated mechanical allodynia and myeloperoxidase mRNA expression. Conclusion: bFGF increased in spinal microglia during the development allodynia after spinal nerve ligation. Thus, controlling bFGF release from microglia during the acute stage of peripheral nerve injury may suppress the progression of allodynia. Level of Evidence: N/A